mHealth and eHealth Applications for a Medicalized Quarantine Hotel during the COVID-19 Pandemic - Lin, Shu-Chuan; Yeh, Hui-Tzu; Lee, Yu-Hsia; Hsu, Suh-Meei (Applied Clinical Informatics, 2023)
Background In Taiwan, the number of confirmed cases of coronavirus disease 2019 (COVID-19) has risen significantly in May 2021. The second wave of the epidemic occurred in May 2022. mHealth (mobile health, social media communities) and eHealth (electronic health, Hospital Information System) can play an important role in this pandemic by minimizing the spread of the virus, leveraging health care providers' time, and alleviating the challenges of medical education.Objectives This study aimed to describe the process of using mHealth and eHealth to build a medicalized quarantine hotel (MQH) and understand the physical and mental impact of COVID-19 on patients admitted to the MQH.Methods In this retrospective observational study, data from 357 patients who stayed at the MQH were collected and their psychological symptoms were assessed using an online Brief Symptom Rating Scale (BSRS). Descriptive statistics, independent sample t-test, univariate analysis of variance, and multiple linear regression analysis were performed.Results The patients' mean age was 35.5  ±   17.6 years, and 52.1% (n  =  186) of them were males. Altogether, 25.2% (n  =  90) of the patients had virtual visits. The average duration of the hotel stay was 6.8  ±   1.4 days, and five patients (0.01%) were transferred to the hospital. The three most common symptoms reported were cough (39%), followed by the sore throat (22.8%), and stuffy/runny nose (18.9%). Most patients achieved a total BSRS score of 0 to 5 points (3,569/91.0%), with trouble falling asleep (0.65  ±   0.65), feeling tense or high-strung (0.31  ±   0.66), and feeling down or depressed (0.27  ±   0.62) scoring highest. The BSRS score was the highest on the first day. The sex of the patients was significantly related to the BSRS score (p  <  0.001).Conclusion mHealth and eHealth can be used to further monitor an individual's physiological and psychological states. Early intervention measures are needed to improve health care quality.
Keywords: Quarantine Hotel; electronic health systems; mobile application; psychological distress; COVID-19